2005
DOI: 10.1007/s10891-005-0043-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the parameters of a nonstationary arc spot on a copper cathode by the thermospectroscopic method. I. Current density

Abstract: A new procedure of determination of the effective density of the current in a nonstationary arc spot with the use of thermophysical and spectroscopic measurements has been proposed and tested. The procedure is based on recording of the critical cathode temperature corresponding to the instant of sharp increase in the intensity of the CuI λ = 5218 A° atomic spectral line, which coincides with the beginning of intense emission of a copper vapor from the spot, according the hypothesis proposed. New results are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…At high current (up to several kA) and long discharge distance, several cathode spots exist simultaneously. Bublievskii and Kesaev [17] found that when the current exceeded a threshold current, the single arc spot split into multiple cathode spots of branch-like character. Martin et al [18] studied the reason for the movement of the split spots.…”
Section: Introductionmentioning
confidence: 99%
“…At high current (up to several kA) and long discharge distance, several cathode spots exist simultaneously. Bublievskii and Kesaev [17] found that when the current exceeded a threshold current, the single arc spot split into multiple cathode spots of branch-like character. Martin et al [18] studied the reason for the movement of the split spots.…”
Section: Introductionmentioning
confidence: 99%